2016
DOI: 10.1097/jcn.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Counseling in Patients With Heart Failure

Abstract: Cardiac nurses in Germany rarely practice sexual counseling. It is a phenomenon that is silent. Education and skill-based training might hold potential to "break the silence."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Whereas previous studies have reported healthcare professionals’ reluctance or difficulty with providing sexual counseling, 10 , 33 staff were, on the whole, comfortable with delivering the content of the patient education class on sexual health. Nevertheless, some concerns persisted that a discussion on sexual matters might embarrass or make patients uncomfortable.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Whereas previous studies have reported healthcare professionals’ reluctance or difficulty with providing sexual counseling, 10 , 33 staff were, on the whole, comfortable with delivering the content of the patient education class on sexual health. Nevertheless, some concerns persisted that a discussion on sexual matters might embarrass or make patients uncomfortable.…”
Section: Discussionmentioning
confidence: 83%
“… 7 Two key reasons for this have been identified: first, the personal and sensitive nature of the topic that prohibits patients from raising the issue 8 and, second, the unpreparedness of health professionals in terms of lack of training, knowledge, comfort, and skills to confidently discuss sexual health problems with their cardiac patients. 9 , 10 …”
mentioning
confidence: 99%
“…The existence of negative behaviors and beliefs, as well as the perception of having little training in matters of sex, can hamper work on aspects related to sex in primary care consultations (Dalfó Pibernat, Pelegrina Rodríguez, Dalfó Pibernat, Rosell Vidal, & Rosell Vidal, ). It has been reported that most nurses do not consider sexual education as necessary to practice their profession, and consequently, they do not provide it (Kolbe, Kugler, Schnepp, & Jaarsma, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of health care professionals feel a certain responsibility to discuss patients' sexual health, in practice, they seldom address sex with their patients, even during cardiac rehabilitation or in general practice 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Some feel embarrassed to address the topic, others do not want to embarrass the health care providers, or others fear that their health care provider is not experienced enough to understand his/her problems 9, 11…”
Section: Introductionmentioning
confidence: 99%